A Case of Combined Central and Peripheral Demyelination Associated With Antineurofascin 155 Antibodies and Paternal History of Multiple Sclerosis. Issue 4 (July 2021) - Lambrianides, Sakis; Kinnis, Evgenios; Cleanthous, Michele; Myrianthopoulou, Panayiota; Leonidou, Eleni; Kyriakides, Theodoros
Abstract : Introduction: Combined central and peripheral demyelination (CCPD) is a term used to describe a rare condition involving demyelinating lesions of both the central and the peripheral nervous system. Its etiology remains unclear, and a pathogenic role of cell-mediated and/or humoral immunity has been proposed. A number of patients with CCPD are positive to antineurofascin (anti-NF), antigalactocerebroside, and antilactosylseramide antibodies. The relation between CCPD and multiple sclerosis (MS) is unclear. Case Report: We report the case of a 30-year-old man who was referred for evaluation after having episodes of numbness and gait impairment worsened by intravenous Methylprednisolone and was found to have demyelination in both central and peripheral nervous system. The patient was eventually diagnosed with anti-NF 155 CCPD and received multiple courses of intravenous immunoglobulin without significant improvement, while he remained stable under Rituximab. Interestingly, the patient's father suffered from a mild form of relapsing remitting MS. Conclusion: Our case emphasizes that clinicians need to keep in mind the possibility of a coexisting demyelination in both central and peripheral nervous system, even in patients with a family history of MS. The need for a timely diagnosis is imperative since several drugs used in the management of MS can worsen the patient's symptoms in CCPD. This is, to our knowledge, the first reported case of a patient with anti-NF 155 positive CCPD and a family history of MS.